Education About Medicine and Utilization Of Carrot (Daucus carota L.) Agricultural Residuals as Skin Moisturizing Soap in Rumah Berastagi Village, Karo District: Edukasi Tentang Obat dan Pemanfaatan Sisa Hasil Pertanian Buah Wortel (Daucus carota L.) Sebagai Sabun Pelembap Kulit Di Desa Rumah Berastagi Kabupaten Karo - Sumaiyah, Sumaiyah; Sormin, Tessa; Nadaresta, Maria; Ni Rudang, Singgar; Ismanelly Hanum, T.; Sri Rohani, Ade; Nurhaz Siregar, Arfah; Putri Yolanda Barus, Dwi (Universitas Haji Sumatera Utara, 2025)
The community service activity aimed to increase the community's knowledge about medicines and provide a workshop on making solid soap using carrots as an innovation for moisturizing soap, thereby increasing the income of the villagers in Rumah Berastagi, Karo Regency, North Sumatra. The method used in this community service was counseling and product training using the modified Community-Based Interactive Approach (CBIA) method, where participants, who were representatives of the community, were actively involved throughout the activity. This activity was evaluated through the results of pre-test and post-test questionnaires and was analyzed descriptively both qualitatively and quantitatively. The analysis of the pre-test and post-test results showed that there was an increase in the community's knowledge and skills. This was evidenced by the data, with participants' scores increasing from 72.66 before the service activity to 88.33 afterward. The education and workshop provided successfully enhanced the community's knowledge about medicines, the benefits of carrot content, marketing and business planning, as well as their skills in making solid soap.